Analisis Pengaruh Social Media Marketing Melalui Instagram Terhadap Brand Awareness Fish Sambal - Arimbawa, I Kadek Aditya; Satriawan, I Ketut; Lani Triani, I Gusti Ayu (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 8 No 2 (2023)DO - 10.24843/JITPA/2023.v08.i02.p07, 2023)
Fish Sambal is a seafood chili brand from Nusa Penida which markets its products through Instagram-based social media. However, there was a decrease in Instagram Fish Sambal performance in August-November 2022 compared to May-July 2022. The purpose of this study was to identify Fish Sambal's social media marketing strategy, analyze the effect of social media marketing on Fish Sambal's brand awareness and make suggestions for alternative social strategies. media marketing to increase brand awareness of Fish Sambal. In-depth interviews with Fish Sambal internal parties were conducted to identify the 4C social media marketing, the Structural Equation Modeling-Partial Least Square (SEM-PLS) method was used to analyze the effect of social media marketing on Fish Sambal brand awareness and the FGD method was used to make social media strategy proposals marketing. The results showed that Fish Sambal brand awareness was influenced by social media marketing and social media marketing dimensions consisting of context, communication, collaboration, and connection which could explain brand awareness of 58.9% and 41.1% explained by other dimensions outside the model. The proposed social media marketing strategy is on the context dimension; advertisement planner, maximizing Instagram features and determining when to upload content. Communications; carry out social media campaigns and carry out direct marketing. Collaboration; collaborate with influencers and other brands. Connections; create a membership program.   Keyword: social media marketing, brand awareness, Structural Equation Modeling-Partial Least Square (SEM-PLS).